2020
DOI: 10.1017/nps.2019.104
|View full text |Cite
|
Sign up to set email alerts
|

Food and Nationalism: Gastronationalism Revisited

Abstract: This article reviews recent developments in scholarship on gastronationalism, or more broadly, food and nationalism. It finds while the concept of gastronationalism per se has not been rigorously developed, scholarship of food and nationalism in general has been developing fast. A major development in the study of gastronationalism is the introduction of the everyday nationhood/banal nationalism perspective, which in turn diverts the focus away from the state’s intervention, a point emphasized by Michaela DeSo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…Social entrepreneurs capitalize on customer motivations related to their local resources and values by creating imagery associations between their distinctive local identity and/or social cause, creating an inimitable producer's brand-identity (Müller & Korsgaard, 2018). Building an identity based on physical resources (historic buildings, legends, or natural products) and owner personalities or talents can create a complex relationship between the community and local food producers (Ichijo, 2020). Marketing literature has long recognized the strong impact local culture and national heritage have on a producer's brand identity (Pike, 2013), and France's gastronomic, cultural heritage characterizes this, with their nation's economy and identity closely linked to food producers and their town, area, and/or region (Ichijo, 2020).…”
Section: Producer Identitymentioning
confidence: 99%
See 4 more Smart Citations
“…Social entrepreneurs capitalize on customer motivations related to their local resources and values by creating imagery associations between their distinctive local identity and/or social cause, creating an inimitable producer's brand-identity (Müller & Korsgaard, 2018). Building an identity based on physical resources (historic buildings, legends, or natural products) and owner personalities or talents can create a complex relationship between the community and local food producers (Ichijo, 2020). Marketing literature has long recognized the strong impact local culture and national heritage have on a producer's brand identity (Pike, 2013), and France's gastronomic, cultural heritage characterizes this, with their nation's economy and identity closely linked to food producers and their town, area, and/or region (Ichijo, 2020).…”
Section: Producer Identitymentioning
confidence: 99%
“…Building an identity based on physical resources (historic buildings, legends, or natural products) and owner personalities or talents can create a complex relationship between the community and local food producers (Ichijo, 2020). Marketing literature has long recognized the strong impact local culture and national heritage have on a producer's brand identity (Pike, 2013), and France's gastronomic, cultural heritage characterizes this, with their nation's economy and identity closely linked to food producers and their town, area, and/or region (Ichijo, 2020). A French study found that consumers identified the relationship to cooperative products and resource acquisition as more positive than the ones to traditional for-profit companies (Faure-Ferlet et al, 2018).…”
Section: Producer Identitymentioning
confidence: 99%
See 3 more Smart Citations